2019
DOI: 10.1039/c9tc03632f
|View full text |Cite
|
Sign up to set email alerts
|

Facile one-pot synthesis of long-term thermally stable CDs@AlOOH toward white-light illumination

Abstract: The CDs doped boehmite composite (CDs@AlOOH) is directly achieved through a facile, low-cost and green one-step decomposition route with tunable fluorescence emission and long-term thermal stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…In Figure , phytic acid was used as a precursor and a doping source of the CDs, graphene oxide (GO) was used to anchor CDs, and after a heating treatment without breaking the morphology of CDs, the composite showed excellent oxygen reduction reaction (ORR) performance with a high P‐doping content due to the anchoring mechanism of CDs on the substrate. And in Wang's work, [ 131 ] to synthesize high‐efficient matrix encapsulated carbon dots materials and to avoid preparation complexity, aluminum glycine was utilized as a precursor and followed with a heating treatment in different atmospheres through the one‐step synthesis of CDs doped boehmite composite (CDs@AlOOH). The uniformly dispersed CDs anchored on AlOOH effectively reduced the self‐quenching effect of CDs and enhanced the fluorescence properties.…”
Section: Novel Synthesis Of Cds/xmentioning
confidence: 99%
“…In Figure , phytic acid was used as a precursor and a doping source of the CDs, graphene oxide (GO) was used to anchor CDs, and after a heating treatment without breaking the morphology of CDs, the composite showed excellent oxygen reduction reaction (ORR) performance with a high P‐doping content due to the anchoring mechanism of CDs on the substrate. And in Wang's work, [ 131 ] to synthesize high‐efficient matrix encapsulated carbon dots materials and to avoid preparation complexity, aluminum glycine was utilized as a precursor and followed with a heating treatment in different atmospheres through the one‐step synthesis of CDs doped boehmite composite (CDs@AlOOH). The uniformly dispersed CDs anchored on AlOOH effectively reduced the self‐quenching effect of CDs and enhanced the fluorescence properties.…”
Section: Novel Synthesis Of Cds/xmentioning
confidence: 99%
“…[11] Nevertheless, due to the uniformity of surface functional groups, the lack of diversified active sites and low quantum yield limit the application development. [12] Therefore, it is necessary to change the surface state of CDs through functionalization to expand the scope of application, which has become the focus of current research. [13,14] In particularly, surface modifications can improve the targeting selectivity of CDs Parker equation verified that the process was internal filtration effect (IFE) and fluorescence resonance energy transfer (FRET), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 ] CDs are broadly used in sensors, [ 14,15 ] cell imaging, [ 16,17 ] fluorescent ink, [ 18 ] and drug delivery [ 19 ] due to their excellent stable luminescence, low cost, facile surface modification, tunable emission, nontoxicity, water solubility, and biocompatibility. [ 20,21 ] Several published papers have discussed the application of CDs in adsorption; Seema and colleagues [ 22 ] reported a polyurethane sponge embedded in polydimethylsiloxane and CDs to investigate its oil absorption performance. The results showed that the addition of CDs can significantly improve the oil absorption capacity.…”
Section: Introductionmentioning
confidence: 99%